Sustainability of Project-Based Learning: Challenge and Obstacles from Students Perception Point of View - Sylva Sagita; Adi Rahmat; Didik Priyandoko; Siti Sriyati (Postgraduate, University of Mataram, 2023)
The Covid-19 pandemic has caused students to experience learning loss or a slowdown in student learning development in literacy, numeracy, and science. Another pandemic's impact is changing students' behavior and emotions, such as difficulty concentrating during online learning, sensitivity, anxiety, and other excessive worries. In order to overcome learning problems, one strategy from the government is releasingÂ Kurikulum Merdeka, which focuses on Project-based learning. Several studies discussed the difficulties of project learning from the teacher's view, but no data explicitly discusses students' difficulty in implementing project learning. This research aims to identify the challenges and obstacles experienced by students when carrying out project learning. Furthermore, this research is grounded research used as reflection material for teachers in planning and improving the quality of project-based learning. The Project Learning Experience questionnaire was distributed to seven high schools in Kota Bandung, and 592 responses were recorded. From the data findings, students faced challenges in collaborative activities; contributions, time management, problem-solving, teamwork, and investigation techniques due to a lack of self-regulation. Theoretical contributions and implications for educational practices are discussed